A Comparison of the Temperature Regime of Short Stream Segments under Forested and Non‐Forested Riparian Zones at Eleven Sites Across North America. (7th August 2014) - Simmons, J. A.; Anderson, M.; Dress, W.; Hanna, C.; Hornbach, D. J.; Janmaat, A.; Kuserk, F.; March, J. G.; Murray, T.; Niedzwiecki, J.; Panvini, D.; Pohlad, B.; et al.
Abstract When forested riparian zones are cleared for agriculture or development, major changes can occur in the stream temperature regime and consequently in ecosystem structure and function. Our main objective was to compare the summer temperature regimes of streams with and without forest canopy cover at multiple sites. The secondary objective was to identify the components of the stream heat budget that had the greatest influence on the stream temperature regime. Paired stream reaches (one forested and one non‐forested or 'open') were identified at 11 sites distributed across the USA and Canada. Stream temperature was monitored at the upstream and downstream ends of 80 to 130‐m‐long reaches during summer, and five variables were calculated to describe the stream temperature regime. Overall, compared with forested reaches, open reaches tended to have significantly higher daily mean (mean difference = 0.33 ± 1.1°C) and daily maximum (mean difference = 1.0 ± 1.7°C) temperatures and wider daily ranges (mean difference = 1.1 ± 1.7°C). Mean and maximum daily net heat fluxes in open reaches tended to be greater (or less negative) than those in forested reaches. However, certain sites showed the opposite trends in some variables because of the following: (i) Daily mean and maximum temperatures were biased by differences in inflow temperature between paired reaches and (ii) inputs of cold groundwater exerted a strong influence on temperature. Modelling and regression results suggested that within sites, differences in direct solar radiation were mainly responsible for the observed differences in stream temperature variables at the daily scale. © 2014 The Authors. River Research and Applications published by John Wiley & Sons, Ltd.